Contributions of an extension project during a COVID-19 pandemic: experience report (Research, Society and Development, 2022)
Objective: Discuss the contributions and impacts of the “Alô, Comunidade” university extension for extension workers and society. Method: Descriptive study of a qualitative approach, in the experience report modality, developed from the experiences and experiences of creating and posting podcasts provided by the extension action itself. Results: In this first phase of the extension, 10 informative podcasts were produced, aimed at disseminating knowledge about health education contextualized in the pandemic scenario caused by the new coronavirus (SARS-CoV-2). The podcasts were structured and recorded by extension workers with guidance from teachers and disseminated through social networks. Conclusion: The actions built and developed through the extension project “Alô, Comunidade” have become important teaching and learning strategies in the current period. The dissemination of knowledge within the health area, through the use of digital information and communication resources, benefited listeners and extension workers. In addition, essential skills were developed for the students' future professional practice, such as communication, teamwork and technological mastery.